2004
DOI: 10.1136/bmj.38181.482222.55
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids for severe sepsis and septic shock: a systematic review and meta-analysis

Abstract: Objective To assess the effects of corticosteroids on mortality in patients with severe sepsis and septic shock. Data sources Randomised and quasi-randomised trials of corticosteroids versus placebo (or supportive treatment alone) retrieved from the Cochrane infectious diseases group's trials register, the Cochrane central register of controlled trials, Medline, Embase, and LILACS. Review method Two pairs of reviewers agreed on eligibility of trials. One reviewer entered data on to the computer and four review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
258
3
9

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 410 publications
(277 citation statements)
references
References 33 publications
7
258
3
9
Order By: Relevance
“…The administration of steroids emerged as a treatment option suited to this particular pathophysiology and was adopted into the Surviving Sepsis Campaign Guidelines (SSCG) 2004,153 according to the concept of “relative adrenal insufficiency.” Since then, however, the adrenocorticotropic hormone (ACTH) stimulation test was proved not to be useful in identifying corticosteroid‐responsive patients, partly because the concentration of free cortisol, actually present in vivo , could not be measured or estimated by a measurement of total cortisol concentration, and therefore the rapid ACTH stimulation test was “not recommended” (class 2B) in SSCG 2008 154. In studies assessing the effect of low‐dose corticosteroids in patients with sepsis of various severities, their effectiveness was observed only in critically‐ill patients with septic shock 155, 156. In 2016, Keh et al .…”
Section: Introductionmentioning
confidence: 99%
“…The administration of steroids emerged as a treatment option suited to this particular pathophysiology and was adopted into the Surviving Sepsis Campaign Guidelines (SSCG) 2004,153 according to the concept of “relative adrenal insufficiency.” Since then, however, the adrenocorticotropic hormone (ACTH) stimulation test was proved not to be useful in identifying corticosteroid‐responsive patients, partly because the concentration of free cortisol, actually present in vivo , could not be measured or estimated by a measurement of total cortisol concentration, and therefore the rapid ACTH stimulation test was “not recommended” (class 2B) in SSCG 2008 154. In studies assessing the effect of low‐dose corticosteroids in patients with sepsis of various severities, their effectiveness was observed only in critically‐ill patients with septic shock 155, 156. In 2016, Keh et al .…”
Section: Introductionmentioning
confidence: 99%
“…Adrenalectomized animals face a lethal risk to inflammatory challenges that are normally nonlethal (Hinshaw et al, 1985), and recent evidence suggests that intermittent and tapered low doses of corticosteroid can improve outcome in septic patients (Annane et al, 2004;Minneci et al, 2004). Thus, the endogenous adrenocortical response to sepsis appears in some way inadequate as a natural defense mechanism, and the central neural response to sepsis may contribute to this inadequacy.…”
Section: Introductionmentioning
confidence: 99%
“…Dans une importante méta-analyse incluant principalement des patients adultes, les auteurs ont découvert que les patients septiques à qui l'on avait donné des corticostéroïdes à court terme (un à trois jours) ne montraient aucune différence en matière de mortalité à 28 jours, toutes causes confondues, par rapport aux témoins. 29 La plupart des études abordant la question de l'utilisation de corticostéroïdes pour traiter le sepsis portent sur des patients adultes; toutefois, dans une étude randomisée contrôlée, on a administré une dose de 0,20 mgÁkg -1 de dexaméthasone à des enfants atteints de sepsis toutes les huit heures pendant deux jours, et les résultats n'ont pas montré de différence en matière de mortalité. 30 Comme il n'existe pas de données probantes convaincantes selon lesquelles l'utilisation à court terme de doses élevées de corticostéroïdes serait néfaste pour les patients septiques, il est peu probable que la dexaméthasone aggrave une infection, quelle qu'elle soit, chez la plupart des patients en chirurgie.…”
Section: Innocuité Deunclassified
“…In a large meta-analysis of mainly adult patients, the authors found that septic patients given short-term (one to three days) corticosteroids had no difference in 28-day all-cause mortality compared with controls. 29 Most of the literature concerning corticosteroid use in sepsis relates to adult patients; however, in one randomized controlled trial, children with sepsis were administered a 0.20 mgÁkg -1 dose of dexamethasone eight hourly for two days, and results showed no difference in mortality. 30 Seeing as there is no good evidence that the use of short-term high-dose steroids causes harm in septic patients, the chance of dexamethasone exacerbating any kind of infection in most surgical patients is unlikely.…”
mentioning
confidence: 99%